Patient stakeholder engagement in research: A narrative review to describe foundational principles and best practice activities. (13th February 2019) - Harrison, James D.; Auerbach, Andrew D.; Anderson, Wendy; Fagan, Maureen; Carnie, Martha; Hanson, Catherine; Banta, Jim; Symczak, Gina; Robinson, Edmondo; Schnipper, Jeffrey; Wong, Celene; Weiss, Rachel
Abstract: Background: Health research is evolving to include patient stakeholders (patients, families and caregivers) as active members of research teams. Frameworks describing the conceptual foundations underlying this engagement and strategies detailing best practice activities to facilitate engagement have been published to guide these efforts. Objective: The aims of this narrative review are to identify, quantify and summarize (a) the conceptual foundational principles of patient stakeholder engagement in research and (b) best practice activities to support these efforts. Search Strategy, Inclusion Criteria, Data Extraction and Synthesis: We accessed a publicly available repository of systematically identified literature related to patient engagement in research. Two reviewers independently screened articles to identify relevant articles and abstracted data. Main Results: We identified 990 potentially relevant articles of which 935 (94.4%) were excluded and 55 (5.6%) relevant. The most commonly reported foundational principles were "respect" (n = 25, 45%) and "equitable power between all team members" (n = 21, 38%). Creating "trust between patient stakeholders and researchers" was described in 17 (31%) articles. Twenty‐seven (49%) articles emphasized the importance of providing training and education for both patient stakeholder and researchers. Providing financial compensation for patient stakeholders' time and expertise was noted in 19 (35%) articles. Twenty articles (36%) emphasized regular, bidirectional dialogue between patient partners and researchers as important for successful engagement. Discussion and Conclusions: Engaging patient stakeholders in research as partners presents an opportunity to design, implement and disseminate patient‐centred research. This review creates an overarching foundational framework for authentic and sustainable partnerships between patient stakeholders and researchers.